A novel KIF5A gene variant causes spastic paraplegia and cerebellar ataxia. Issue 11 (17th September 2018) - Qiu, Yusen; Zhong, Shanshan; Cong, Lu; Xin, Ling; Gao, Xuguang; Zhang, Jun; Hong, Daojun
Abstract: Mutations in the kinesin family member 5A ( KIF5A ) gene are mainly associated with autosomal dominant spastic paraplegia 10 (SPG10). The additional complicated symptoms of SPG10 commonly include a wide spectrum. However, cerebellar ataxia is only noticed in a very few patients. Herein, we described a large autosomal dominant family, in which the affected individuals presented with progressive spastic paraparesis and marked cerebellar ataxia. Exome sequencing revealed that a novel variant in the KIF5A gene might be responsible for the phenotype. The obvious cerebellar ataxia indicated that the KIF5A gene should be included in the expanding gene list for spasticity‐ataxia spectrum.